Asymptomatic urethral lymphogranuloma venereum: a case report. (July 2018) - Charest, Louise; Fafard, Judith; Greenwald, Zoë R
Since 2003, there has been a resurgence of lymphogranuloma venereum (LGV), a variant of Chlamydia trachomatis (CT), among men who have sex with men (MSM) in several urban areas of Europe and North America. LGV infection occurs most often at anal sites causing proctitis. Urethral and oropharyngeal infections are rare. In Quebec, LGV incidence has been increasing exponentially in recent years and the current guidelines support systematic LGV genotype testing among anorectal CT-positive samples only. This case report describes a patient with a urethral LGV infection, remarkable due to its prolonged asymptomatic development prior to the manifestation of an inguinal bubo. Physicians should be vigilant of potential cases of LGV and forward CT-positive samples occurring among individuals with LGV risk factors for genotype testing.